IS THERE ANY FORESTRY EDUCATION IN ROMANIA? GEOGRAPHY TEACHERS' PERCEPTIONS, ATTITUDES, AND RECOMMENDATIONS - MARIA ELIZA DULAMĂ; OANA-RAMONA ILOVAN; IOANA MAGDAŞ; BIANCA SORINA RĂCĂŞAN (Studia Universitatis Babes-Bolyai, 2016)
ABSTRACT. The problem our study found a solution for was the lack of efficient forestry education in Romania. In this context, studies argued that many of the citizens' attitudes towards forests formed during teachers' organized activities. Because the efficiency of those activities for forestry education depended on the school curriculum and on the Geography teachers' training, beliefs, and attitudes, in our research, by administering a questionnaire to 208 Geography teachers, we wanted to identify: their perceptions of the impact certain factors had, of certain activities efficiency and of certain components in the Geography school curricula; the approach of forest topics in official documents; teachers' involvement of their students in diverse activities; their opinions on forest topics that should have been included in the official curriculum. For forestry education in Romania, they perceived school and family as having the biggest impact, and the activities in the forests as the most efficient ones. Research showed that Romanian Geography teachers participated frequently at actions that focused on forestry education. They perceived as weak and very weak the approach of forest topics and their protection in diverse official education documents, and because of this they recommended improvement, suggesting relevant themes, in compliance with the forestry literature.